2008
DOI: 10.1007/s00464-008-9938-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical usefulness of indocyanine green as an alternative to India ink for endoscopic marking

Abstract: This study supports the use of ICG as a safe technique that can be identified reliably during operations performed within 8 days after endoscopic injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 21 publications
1
78
0
Order By: Relevance
“…Preoperative tattooing with dye injection is probably the simplest of these, and is often used in colon surgery [17][18][19]. However, as observed in this study, the injected dye can easily spread across the serosal surface in the case of gastric surgery, which sometimes makes it difficult to …”
Section: Discussionmentioning
confidence: 93%
“…Preoperative tattooing with dye injection is probably the simplest of these, and is often used in colon surgery [17][18][19]. However, as observed in this study, the injected dye can easily spread across the serosal surface in the case of gastric surgery, which sometimes makes it difficult to …”
Section: Discussionmentioning
confidence: 93%
“…ICG enables rapid intraoperative visualisation of SLNs and lymphatic drainage in patients with breast and early gastric cancer [5-7, 15]. ICG was initially recommended as a tattooing agent for colonic lesions to aid perioperative localisation [16-18] as there were no reports of complications such as focal peritonitis, abscess formation, postoperative adhesions, and ileus seen with the use of India ink [19-21]. However, its use as a tattooing agent is limited to patients undergoing surgery within 8 days after endoscopic injection, as the dye dissipates through lymphatic channels due to its small molecular size [16].…”
Section: Resultsmentioning
confidence: 99%
“…ICG was initially recommended as a tattooing agent for colonic lesions to aid perioperative localisation [16-18] as there were no reports of complications such as focal peritonitis, abscess formation, postoperative adhesions, and ileus seen with the use of India ink [19-21]. However, its use as a tattooing agent is limited to patients undergoing surgery within 8 days after endoscopic injection, as the dye dissipates through lymphatic channels due to its small molecular size [16]. More recently, its fluorescence properties have been utilised for intraoperative localisation of colorectal neoplasms and associated SLNs [22-26] in patients undergoing surgery.…”
Section: Resultsmentioning
confidence: 99%
“…The tumor site could not be visually recognized after an interval of 5 days in 1 patient who was obese with BMI of 27.3. A previous report stated that ICG visibility was dependent not only on the interval between endoscopic marking and surgery but also on other factors, such as the thickness of pericolonic fat, omentum, mesentery, and the posterior abdominal wall [17] . In this study, we injected ICG only at the distal side of the tumor regardless of the location of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Miyoshi et al [17] suggested that the duration of ICG visibility was up to 8 days after injection, if ICG was used as a green dye. The ICG concentration used in that study was 1.25%, and the ICG used by Lee et al [18] and Price et al [9] were 1 and 1.25%, respectively, if it was used as a green dye.…”
Section: Discussionmentioning
confidence: 99%